Strategi Manajemen Keuangan Dalam Meningkatkan Kesejahteraan Sekolah Dasar Islam Terpadu Di Banjarmasin - Riinawati; Ahmad Salabi (Jurnal Visionida, 2024)
This study aims to evaluate the impact of implementing financial management strategies at SDIT XYZ Banjarmasin Integrated Islamic Primary School on the welfare of students, teachers and staff as well as the effectiveness of school fund allocation in creating a learning environment that supports student development. A combined approach was used with quantitative analysis to measure financial efficiency and qualitative analysis through interviews and observations. The financial management strategies implemented had a significant positive impact. School funds are allocated efficiently to support extracurricular activities, purchase quality learning materials and improve educational facilities. The focus on teacher and staff welfare through personal development incentives and wellness programs creates a positive working environment. The implications of the findings are highly relevant for policy development in education and school financial management. Best practices can be adopted to improve student and staff welfare through smart allocation of funds. Further strategic planning is needed to improve the quality of education by taking into account the welfare of the entire school community. Schools can more effectively achieve their educational goals by building an empowering and sustainable learning environment and improving financial management practices that support student and staff welfare. Penelitian ini bertujuan untuk mengevaluasi dampak implementasi strategi manajemen keuangan di Sekolah Dasar Islam Terpadu SDIT XYZ Banjarmasin terhadap kesejahteraan siswa, guru, dan staf serta efektivitas alokasi dana sekolah dalam menciptakan lingkungan pembelajaran yang mendukung perkembangan siswa. Pendekatan gabungan digunakan dengan analisis kuantitatif untuk mengukur efisiensi keuangan dan analisis kualitatif melalui wawancara dan observasi. Strategi manajemen keuangan yang diterapkan memberikan dampak positif signifikan. Dana sekolah dialokasikan dengan efisien untuk mendukung kegiatan ekstrakurikuler, membeli materi pembelajaran berkualitas, dan meningkatkan sarana pendidikan. Fokus pada kesejahteraan guru dan staf melalui insentif pengembangan diri dan program kesehatan menciptakan lingkungan kerja yang positif. Implikasi dari temuan ini sangat relevan untuk pengembangan kebijakan di bidang pendidikan dan manajemen keuangan sekolah. Praktik-praktik terbaik dapat diadopsi untuk meningkatkan kesejahteraan siswa dan staf melalui alokasi dana yang cerdas. Perencanaan strategis lebih lanjut diperlukan untuk meningkatkan kualitas pendidikan dengan memperhatikan aspek kesejahteraan seluruh komunitas sekolah. Sekolah dapat lebih efektif mencapai tujuan pendidikan dengan membangun lingkungan belajar yang berdaya guna dan berkelanjutan, serta meningkatkan praktik manajemen keuangan yang mendukung kesejahteraan siswa dan staf.